The Role of Social Media in Preventing HIV/AIDS: A Systematic Review - Pinto, Joaquim; De Jesus Leite, Ana Do Rosário; Gaio, Eduardo Crisogsono; Alves, Maria Manuela; de Carvalho, Joaquim Gregorio; Tilman, Carlos Boavida (West Science Interdisciplinary Studies, 2025)
The increasing prevalence of social media has transformed health communication practices and created new opportunities for HIV/AIDS prevention. This study aims to systematically examine the role of social media in preventing HIV/AIDS by synthesizing findings from existing academic literature. A systematic literature review approach was employed, analyzing fifteen peer-reviewed studies retrieved from Google Scholar that focus on the use of social media platforms in HIV/AIDS prevention efforts. The review findings indicate that social media plays a significant role in enhancing HIV/AIDS awareness and knowledge, shaping positive attitudes toward prevention, encouraging HIV testing and safer sexual behaviors, and reducing stigma among diverse populations, particularly adolescents, young adults, and key risk groups. Interactive content, peer-to-peer communication, and platform-specific engagement strategies were identified as critical factors in intervention effectiveness. However, the review also reveals persistent challenges, including misinformation, digital inequality, ethical concerns related to privacy, and limited evidence of long-term behavioral impact. Overall, the study concludes that social media serves as an effective complementary tool for HIV/AIDS prevention when integrated with broader public health strategies, while emphasizing the need for more rigorous and longitudinal research to strengthen evidence-based digital health interventions.⁠